Determinants of Professional Growth of Employees in Nigerian Banking Institutions - Nonye Anefiok Asikpo; Samuel Effiong Affia; Akaninyene Udo Akang (Bina Nusantara University, 2022)
The research examined the determinant of professional growth of employees in Nigerian banking institution. The population of the study consisted of 432 staff of the selected banks in Uyo metropolis. Stratified sampling techniques were used to select 148 respondents out of the population. The instrument used for data collection was questionnaire. The instrument was validated by two experts in evaluation and Test. Data from 148 completed questionnaire forms were subjected to PMC analysis. the findings showed that training and membership with professional body has a remarkable relationship with professional growth of employees in Nigerian banking institution. The study however, recommended that, employees qualified for training should be encouraged by providing study leave with pay, and where scholarship is given a proper contract should be undertaken whereby employees would serve for a certain number of years after his/her course. Emphasis should be placed on in-service training where employees already in the field impact knowledge on the newly employed employees and more effort to be geared towards developing a positive professional attitude among bank staff. Such attitude includes having high regards for the profession, upholding the code of conduct, desisting from any action that can tarnish the image of the profession.